A Drosophila model targets Eiger/TNF? to alleviate obesity-related insulin resistance and macrophage infiltration. - Mirzoyan, Z.; Valenza, A.; Zola, S.; Bonfanti, C.; Arnaboldi, L.; Ferrari, N.; Pollard, J.; Lupi, V.; Cassinelli, M.; Frattaroli, M.; Sahin, M.; Pasini, M.E.; et al. (Disease models & mechanisms, 2023)
Obesity is associated with various metabolic disorders, such as insulin resistance and adipose tissue inflammation (ATM), characterized by macrophage infiltration into adipose cells. This study presents a new Drosophila model to investigate the mechanisms underlying these obesity-related pathologies. We employed genetic manipulation to reduce ecdysone levels to prolong the larval stage. These animals are hyperphagic and exhibit features resembling obesity in mammals, including increased lipid storage, adipocyte hypertrophy and high circulating glucose levels. Moreover, we observed significant infiltration of immune cells (hemocytes) into the fat bodies, accompanied by insulin resistance. We found that attenuation of Eiger/TNF? signaling reduced ATM and improved insulin sensitivity. Furthermore, using metformin and the antioxidants anthocyanins, we ameliorated both phenotypes. Our data highlight evolutionarily conserved mechanisms allowing the development of Drosophila models for discovering therapeutic pathways in adipose tissue immune cell infiltration and insulin resistance. Our model can also provide a platform to perform genetic screens or test the efficacy of therapeutic interventions for diseases such as obesity, type 2 diabetes and non-alcoholic fatty liver disease.